KAJIAN BENTUK STRUKTUR SPASIAL BERDASARKAN POLA PERGERAKAN MASYARAKAT DI KOTA TOMOHON TERKAIT FENOMENA PANDEMI COVID-19 SEBAGAI DASAR PENGEMBANGAN JARINGAN TRANSPORTASI LOKAL - Wenur, Fabian Bill; Rogi, Octavianus H. A.; Poluan, Roosje J (SPASIAL, 2021)
Through a 2020 study, Winda Palindang¹, Octavianus HA Rogi² & Johannes Van Rate³, "Analysis of Tomohon City Transportation Policy Based on Community Movement Plans as an Indicator of City Spatial Structure" researchers identified the type of spatial structure of the city of Tomohon through a dynamic density approach with indicators of people's daily movement patterns as a result. the tendency of a polycentric spatial structure. From this statement, the researcher feels interested in developing this research, still with the same indicators, but by comparing the three periods that are currently happening, namely the period before, during and after the COVID-19 pandemic began to be under control. The purpose of this study is to see whether the state of the COVID-19 pandemic affects the shape of the existing spatial structure as well as to elaborate on the choice of the type of transportation network policy that is compatible with the identified spatial structure. The methods used are quantitative techniques and profit tabulation of origin-destination matrix development with a structured questionnaire or interview format, as well as visualization of the origin-destination matrix in the form of a desire line map or called a "desire line map". The conclusions of this research are; (1) The form of the spatial structure of the city of Tomohon in three types of periods, namely before, during, and after the COVID-19 pandemic has not changed, namely in the form of polycentric. (2) The transportation network policies that need to be considered include: accelerating the execution of the transportation network development plan according to the RTRW of Tomohon City, namely the plan for a type B terminal at the gates of the city of Tomohon, accelerating the procurement of transportation routes between sub-districts. Then the need to strengthen the carrying capacity of local service centers that can be an alternative for community activities to minimize the accumulation of trips to one area. It is recommended for the main corridor of the city of Tomohon to use the concept of a larger mass transportation considering that so many people travel using the main corridor of the city of Tomohon, as well as optimizing microbuses as a mode of transportation for inter-district destinations. And the last is improving the quality of the transportation network for the convenience of its users.Keywords: Spatial Structure, Movement Pattern, Origin-Destination Matrix, Transportation Network